Mapping The Trends Of Inclusive Education In Higher Education: A Bibliometric Review Using R Software - Nisa, Khaerun; Syahwela, Mayu; Tjalla, Awaluddin; Sarifah, Iva; Halifah, Syarifah (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
Inclusive education in higher education, is vital for creating a diverse and equitable learning environment, ensuring equal opportunities for individuals with diverse abilities and backgrounds. This approach enriches the overall educational experience, fostering global readiness in students for a diverse society. This article utilizes bibliometric analysis with R software to track trends in studies concerning the integration of inclusive education in higher education, drawing data from the Scopus database spanning 2013 to 2023. The findings reveal that the growth of scholarly publications on the implementation of inclusive education in higher education experiences fluctuations. The Sustainability Journal (Switzerland) emerges as the most prolific publisher of articles on this subject, with the University of Nottingham being the most productive affiliate. The United States stands out as the most productive country, and the article titled "Sustainability Strategy in Higher Education Institutions: Lessons Learned from a Nine-Year Case Study" by Ramisio et al. holds the distinction of being the most cited. This research outlines inclusive education in higher education for interested scholars, emphasizing current challenges and potential opportunities in implementing it, particularly in Islamic higher education. The article acknowledges limitations that could be addressed through broader metadata sources and a more extended publication timeline. Furthermore, the novelty of this research is no previous researcher has explored inclusive education in higher education using bibliometric analysis.